Powtórzenie w myśli Sorena Kierkegaarda - opowieść a przypowieść - Gołębiewska, Maria (Przestrzenie Teorii, 2007)
In this text the author describes briefly Kierkegaard's conception of existence, which has been juxtaposed by him with the reinterpreted conception of essence and of the existing. Kierkegaard defined existence referring to different orders of representation, first of all to the spoken and written language. He considered existence - always individual and particular - as an object of personal existential choice. This choice concerns, at the same time, the way of individual existence (the stadium of life) and the individual identity. That is why in Kierkegaard's reflection is so important the reference to individual identity and to its grasp in narration - in the mythical parable and in the story concerning everyday life. The problems of existence, identity and their grasp in representation are connected with the Kierkegaardian question of repetition, which is also discussed in this study.